Greenwashing and the Strategy of Real Estate enterprises in the Commercialization of Nature - Silva, Carolline Amaral da; Fonseca, Karolyne Linhares Longchamps; Araujo, Eloisa Carvalho de (Revista Nacional de Gerenciamento de Cidades, 2022)
This essay integrates continued research, with the objective of analyzing the sustainable certifications and greenwashing practice that are being used to validate the exploitation of nature in the interest of capital. Based on a bibliographical and exploratory research of primary and secondary sources, it is proposed to discuss the phenomenon of the exploitation of the natural good and the ecological discourse by the real estate enterprises, bringing as a case study the MARAEY mega-venture, located in the Environmental Protection Area of the city of Maricá, In the state of Rio de Janeiro. In this context, the relation among legislation, urban policy and the maneuvers carried out by the real estate market with the public authorities and regulatory bodies is discussed.